<h2><u>
Answer:</u></h2>
x = 3
y = -8
<h2><u>
Step-by-step explanation:</u></h2>
x + y = -5
x - y = 11
Since the y's will cancel out, we don't need to modify the two equations in any way.
Now, just add the two equations.
x + x = 2x
y + (-y) = 0
-5 + 11 = 6
2x = 6
Divide by 2.
x = 3
To find y, plug 3 in as "x" in one of the two equations.
3 + y = -5
y = -8
Answer: £11.69
Explanation:
1) Work out 2% of £1600:
1600 x 2/100 =36
2) Add it on to the original number to get his new monthly pay:
1600 + 36 = £1636
3) Work out his yearly pay by:
a) finding the amount of months he worked:
46 / 4 = 11.5 months
b) Divide 11.5 into 2 bits and add them on:
1636 x 11 = 17997
1636 x 0.5 = 818
17997 + 818 = £18814
4) To get his pay per week:
18814 / 46 = £409
5) Finally, to get his pay per hour:
409 / 35 = 11.68671...
= £ 11.69
Answer:
-8x + 12
Step-by-step explanation:
Distribute -4 to the parentheses:
-4(2x - 3)
-4(2x) = -8x
-4(-3) = 12
-8x + 12
Answer:
l*b*h is the answer of this question